JTH editorial v17 – The importance of psychosocial factors in transport and health - Charles Musselwhite (Journal of Transport & Health, 2020)
The need to shift out of the car to more active travel is vital for our health. Research into transport and health highlights the need to take into account the wider psychological and social (sometimes referred to as psychosocial) determinants of transport behaviour if we’re to fully understand how to encourage a shift to more safe and more active travel.